Integrasi Aspek Ekonomi dan Lingkungan dalam Perhitungan Produk Domestik Regional Bruto (PDRB) Hijau Subsektor Tanaman Pangan di Kabupaten Barito Kuala - Agustina, Annisa; Nur, Muhammad Anshar (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
This research was conducted to: (1) Identify the value of Depletion, Degradation and Depreciation of the Food Crops Subsector in the Barito Kuala Regency. (2) Knowing the value of Green GRDP in the Agricultural Sector, Food Crops Subsector in Barito Kuala Regency. This research is a descriptive study using quantitative data that follows the concept of green GRDP calculation. This research also comes from secondary data. This research shows that the result of the calculation using the concept of Green GRDP in the Agricultural Sector in the Food Crops Subsector is smaller than the value calculated using the Conventional GRDP concept. The value of Green GRDP of the Agriculture Sector in the Food Crops Subsector in 2016 was 319.5 billion, in 2017 it was 222.1 billion, in 2018 it was 232.7 billion, and in 2019 it was 669.6 billion.